Dichorionic Diamniotic Twin Pregnancy Discordant for Bladder Exstrophy - Tu, William; Chueh, Jane; Kennedy, William (Advances in Urology, 2009)
A 38 year-old woman presented with a dichorionic diamniotic twin pregnancy at gestational age of 32 weeks concerning for an abdominal wall mass in one of the twins. Initial ultrasound evaluation was suspicious for an omphalocele, but the affected twin was found to have bladder exstrophy at birth. This illustrates the difficulties of accurate prenatal diagnosis of bladder exstrophy in a twin pregnancy at a late gestation.